Assessment of Circulating MicroRNAs for the Diagnosis and Disease Activity Evaluation in Patients with Ulcerative Colitis by Using the Nanostring Technology. Issue 11 (November 2015) - Polytarchou, Christos; Oikonomopoulos, Angelos; Mahurkar, Swapna; Touroutoglou, Alexandra; Koukos, Georgios; Hommes, Daniel W.; Iliopoulos, Dimitrios
Abstract : Background: Clinical decision and patient care management in inflammatory bowel diseases is largely based on the assessment of clinical symptoms, while the biomarkers currently in use poorly reflect the actual disease activity. Therefore, the identification of novel biomarkers will serve an unmet clinical need for IBD screening and patient management. We examined the utility of circulating microRNAs for diagnosis and disease activity monitoring in patients with ulcerative colitis (UC). Methods: Blood serum microRNAs were isolated from patients with UC with active and inactive disease and healthy donors. High-throughput microRNA profiling was performed using the Nanostring technology platform. Clinical disease activity was captured by calculating the partial Mayo score. C-reactive protein was measured in patients with UC as part of their clinical monitoring. The profiles of circulating microRNAs and C-reactive protein were correlated with clinical disease indices. Results: We have identified a signature of 12 circulating microRNAs that differentiate patients with UC from control subjects. Moreover, 6 of these microRNAs significantly correlated with UC disease activity. Importantly, a set of 4 microRNAs (hsa-miR-4454, hsa-miR-223-3p, hsa-miR-23a-3p, and hsa-miR-320e), which correlated with UC disease activity were found to have higher sensitivity and specificity values than C-reactive protein. Conclusions: Circulating microRNAs provide a novel diagnostic and prognostic marker for patients with UC. The use of an FDA-approved platform could accelerate the application of microRNA screening in a gastrointenstinal clinical setting. When used in combination with current diagnostic and disease activity assessment modalities, microRNAs could improve both IBD screening and care management. Abstract : Article first published online 6 August 2015.Supplemental Digital Content is Available in the Text.